A Case Report of Haemolytic Disease of Foetus and Newborn due to Anti-E Antibody in a Primigravida Patient (Bangladesh Journal of Medical Science, 2016)
Anti-E antibody is one of the frequently encountered alloantibody of the Rh blood group system; however, it is seldom implicated in haemolytic disease of the foetus and newborn (HDFN). This case report describes a mild HDFN due to anti-E antibody in a full term baby-girl born to a primigravida patient. The baby developed jaundice on the first day of life. Blood group of both mother and the baby was B positive and Rh phenotype was CDe/CDe (R1R1) and CDe/cDE (R1R2) respectively. Anti-E and anti-c was identified in the mother while babys blood showed weak positive Direct Antiglobulin Test with anti-E identified from the babys serum. The baby was started on phototherapy and was discharged well on day-6. Although this was a mild HDFN, we would like to highlight the importance of antenatal screening for pregnant mothers. The antibody screening for Rh-positive mothers is not a routine practice in many centers in Malaysia due to cost-benefit constraints. However, we would like to suggest to include the antenatal red cell antibody screening test for all pregnant mothers at least during the 1st antenatal booking to enable early detection of alloantibody which may cause HDFN, thus enable close monitoring of foetus and initiate early management as needed.Bangladesh Journal of Medical Science Vol.15(1) 2016 p.139-141